Applying Kansei Engineering, the Kano model and QFD to services. (1st January 2013) - Hartono, Markus; Chuan, Tan Kay; Peacock, John Brian
This paper aims to present an integrative framework of Kansei Engineering (KE), the Kano model and quality function deployment (QFD) applied to services. An empirical study involving Indonesian and Singaporean tourists was conducted to showcase the framework's applicability. The study utilises a sample of 100 Indonesian and 125 Singaporean tourists who stayed in luxury hotels and covers only services in luxury hotels. Interviews and face-to-face questionnaire surveys were carried out. Using stepwise linear regression analysis, this research models the effect of perceived hotel service performance on customer emotional needs (Kansei). House of quality (HOQ) is then used to formulate managerial strategies. We present the fruitfulness of integrating the Kano model, KE and QFD. Perceived attractive qualities have a direct significant impact on Kansei response. There is no analysis of the impact of cultural differences on Kansei. We provide insight on which service attributes deserve more attention with regard to their significant impact on customer emotions. It may guide service managers to provide and implement improvement strategies in satisfying customer emotional needs. The study proposes a unique methodology of integrative three concepts commonly used in manufacturing and service quality research to measure and model customer emotional needs.